Improvement of Business Management for SMEs Through Integrated Assitance - Chendrasari Wahyu; Astria Hindratmo; Nur Wahyudi (LPPM Universitas Muhammadiyah Tasikmalaya, 2023)
In the current pandemic conditions, the vanguard as a driving force for the economy is SMEs. The spread of SMEs. The current household scale cannot be separated from an urge to rise in the current pandemic situation. UKM